An Approach to the Soundscapes of Urban Vacant Lands in Lisbon - Paiva, Daniel (2018)
In this paper, we will present preliminary results of our ongoing study on the soundscapes of vacant lands in Lisbon Eastern Zone (LEZ). Our methodology comprised two stages. Firstly, all the vacant lands of Lisbon municipality were identified and georeferenced using remote sensing methods and high-resolution aerial photography. In the second stage, a field survey with the purpose of characterising the morphology, vegetation, and animal and human occupation of the vacant lands was conducted, along with field recordings of their soundscapes. The results of our study include the classification of vacant lands and of their soundscapes. We argue that listening to the sounds of urban vacant lands defies traditional notions of the urban soundscape as dominated by anthrophonies.